1997
DOI: 10.1006/inco.1997.2659
|View full text |Cite
|
Sign up to set email alerts
|

Context-Sensitive String Languages and Recognizable Picture Languages

Abstract: The theorem stating that the family of frontiers of recognizable tree languages is exactly the family of context-free languages (see J. Mezei and J. B. Wright, 1967, Inform. and Comput. 11, 3 29), is a basic result in the theory of formal languages. In this article, we prove a similar result: the family of frontiers of recognizable picture languages is exactly the family of context-sensitive languages. ] 1997 Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…In 1990's, a robust class of "regular two dimensional languages" has been identified; it may be specified either by tile systems, or by a type of cellular automata, or by a class of monadic second-order formulas, etc. Unfortunately, the class is quite complex -for instance, emptiness property is not decidable, see [21].…”
Section: Related and Future Workmentioning
confidence: 99%
“…In 1990's, a robust class of "regular two dimensional languages" has been identified; it may be specified either by tile systems, or by a type of cellular automata, or by a class of monadic second-order formulas, etc. Unfortunately, the class is quite complex -for instance, emptiness property is not decidable, see [21].…”
Section: Related and Future Workmentioning
confidence: 99%
“…sets of two-dimensional words on finite alphabets [5], called local picture languages. However, by only looking at the words contained in the first row of each picture of a local picture language, one obtains a context-sensitive language, and the converse is true: for any context-sensitive language there exists a local picture language (and a tiling system accepting it) whose set of upper frontiers is that language [8].…”
Section: Arborescent Tiling Systemsmentioning
confidence: 99%
“…They were later characterised as the languages accepted by linearly space-bounded Turing machines [7], i.e. Turing machines whose runs on any input word of length n use at most k·n work tape cells, for some constant k. In [8], it was shown that context-sensitive languages also coincide with the languages accepted by bounded tiling systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sets of pictures are called local picture languages. However, by only looking at the words contained in the first row of each picture of a local picture language, one obtains a context-sensitive language [LS97a].…”
Section: Context Sensitive Languagesmentioning
confidence: 99%